Scintillator cubes for 3D neutrino detector SuperFGD. Issue 1 (1st November 2022) - Fedotov, S; Dergacheva, A; Filik, A; Khabibullin, M; Khotjantsev, A; Kudenko, Yu; Mineev, O; Yershov, N
Abstract : SuperFGD, a highly granular scintillator detector, is under construction to reduce systematic uncertainties in the T2K experiment in order to improve the sensitivity to CP-violation in neutrino oscillations. SuperFGD will be comprised of about 2×10 6 small (10×10×10 mm 3 ) optically isolated polystyrene based plastic scintillator cubes with three orthogonal holes 1.5 mm in diameter. The readout of scintillating light from each cube is provided by three wavelength shifting fibers inserted into the three holes and coupled to MPPC micropixel photosensors. The cubes are covered with a white chemical reflector for optical isolation. The technology of making these cubes, their mechanical properties, their main characteristics obtained during tests with cosmic muons and at the CERN beamline, and the results of the temperature tests are presented in this paper.